Des esclaves et des bêtes : fables de la sauvagerie en Amérique dans Letters from an American Farmer, de St John de Crèvecoeur - Agnès Derail-Imbert (Transatlantica)
The historical naturalist discourse, which serves as an epistemological framework to the narrator of Crèvecœur’s Letters from an American Farmer, draws upon the observation of local animals in order to praise a society of freedom, in which the American farmer’s autonomy depends on the harmonious relationship with his natural environment. This idealized vision is shattered by the horror of slavery which prompts the narrator to conclude that civilization is only a state of nature where man is “an animal of prey” ready to enslave others. In the sequel to this philosophical essay, the narrator resumes his naturalist account with the description of local reptiles, whose murderous behavior hardly fails to evoke slavery, as if servitude and the violence it entails were merely a law of nature. While animal brutality invalidates the myth of a society of sympathy, it nevertheless frees the discourse from its subordination to such utopia, and allows the text to engage with the native figures of American savagery.